Analisis Perbandingan Kinerja Protokol Websocket dengan Protokol SSE pada Teknologi Push Notification - Panser Brigade Muhammad; Widhi Yahya; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Push notification technology allows users (clients) to get information periodically. Information submitted by push notification in the form of notifications such as on social network or news sites. There are many technologies that can be applied to notification delivery. One of them is notification delivery using Websocket protocol and Server-Sent Events (SSE). The Websocket protocol implements full-duplex communication so that either the server or client can send and receive data simultaneously. While the SSE protocol implements half-duplex communication so that the client can only receive data sent server periodically. This study was conducted to compare the performance of Websocket protocol with SSE related to method of delivery of both protocols on push notification technology. Both protocols will be implemented and tested based on predetermined scenarios. The results obtained are the average delay and CPU usage in SSE protocol is smaller than Websocket protocol.